Exacerbation of Pulmonary Fibrosis Following Single Lung Transplantation - Dawei Yang; Jennifer M Wilson; Chunxue Bai; John Yee; Pearce G Wilcox; Nasreen Khalil; Robert D Levy (Canadian Respiratory Journal)
Acute exacerbations of interstitial lung disease present as clinical deteriorations, with progressive hypoxemia and parenchymal consolidation not related to infection, heart failure or thromboembolic disease. Following single lung transplantation, patients receive maintenance immunosuppression, which could mitigate the development of acute exacerbations in the native lung. A 66-year-old man with fibrotic, nonspecific interstitial pneumonitis presented with fever, hypoxemia and parenchymal consolidation limited to the native lung four years after single lung transplantation. Investigations were negative for infection, heart failure and thromboembolic disease. The patient worsened over the course of one week despite broad-spectrum antimicrobial therapy, but subsequently improved promptly with augmentation of prednisone dosed to 50 mg daily and addition of N-acetylcysteine. Hence, the patient fulfilled the criteria for a diagnosis of an acute exacerbation of pulmonary fibrosis in his native lung. Clinicians should consider acute exacerbation of parenchymal lung disease of the native lung in the differential diagnosis of progressive respiratory deterioration following single lung transplantation for pulmonary fibrosis.